The leukotriene d4 receptor antagonist, montelukast, inhibits mast cell degranulation in the dermis induced by water avoidance stress - ERCAN, FERİHA; ÇETİNEL, ŞULE (ELSEVIER GMBH, 2009)
Cysteinyl leukotrienes play a part in inflammatory reactions such as asthma and inflammatory bowel diseases. The leukotrienes exert their actions by binding to and activating various receptors. Montelukast, a leukotriene receptor antagonist, which is used in the treatment of asthma has been shown to be effective in inhibiting the action or formation of leukotrienes. Many skin disorders, such as atopic dermatitis and psoriasis, worsen during stress and seem to be related to infiltration and activation of mast cells that are releasing vasoactive and pro-inflammatory mediators. The aim of the present study was to investigate the effects of montelukast on the degranulation of mast cells in the dermis that is induced by water avoidance stress (WAS). Wistar albino rats were divided into four groups of 8 animals each. Control rats were injected with (1) the vehicle solution or (2) the montelukast solution in the absence of WAS. (3) the WAS group of rats was administered vehicle solution following WAS exposure for 2 h daily for 5 days. (4) The WAS+ML group was administered montelukast 10 mg/kg; i.p. following WAS exposure for 2 h daily for 5 days. Dermal mast cell numbers were determined with toluidine blue and tryptase immunohistochemistry and observed using a light microscope. Numbers of both granulated and degranulated mast cells were significantly increased in the WAS group when compared to control rats. Montelukast treatment decreased the number of both mature granulated and degranulated mast cells in rats subjected to WAS. In conclusion, chronic montelukast treatment reduced WAS-induced infiltration and activation of mast cells in the dermis and may provide a useful therapeutic option in stress-induced skin disorders. (c) 2008 Elsevier GmbH. All rights reserved.
Keywords: Water avoidance stress; Mast cells; Degranulation; Montelukast; CORTICOTROPIN-RELEASING HORMONE; CYSTEINYL LEUKOTRIENES; BLOCKER MONTELUKAST; SKIN; NEUROTENSIN; GENERATION; LESIONS